TRAGIC TIME: RING COMPOSITION AND MYSTERY CULTS IN THE CHORAL SONGS OF SOPHOCLES'ANTIGONE (Argos, 2021)
In this article we aim to recognize ring-composition and to analyze how it is used in Sophocles’ Antigone’s choral songs in connection with the elements from the Eleusinian and the Dionysian cults that pervade the play. Our hypothesis claims that, rather than being a mere factor of formal articulation, ring-composition has a dramatic function because it articulates the allusions to the mysteries through an interplay of parallellisms in order to represent the action as a failed initiation ritual. In the second part we continue the previous analysis and include the remaining choral songs.
Keywords: Ring-composition; Choral song; Antigone; Eleusinian mysteries; Dionysian mysteries